Patumbu Katallassang: Local Wisdom of the Sampulonrua Indigenous Community towards Sustainable Developmant Goals 15 Life on Land - Fitria Wulandari; Khaeruddin Khaeruddin; Hamka Hamza; Nurmiati Nurmiati (UIN Fatmawati Sukarno Bengkulu, 2025)
The Earth faces the threat of destruction due to human activities, such as carbon dioxide emissions of 200 tons per second, destruction of 750 tons of topsoil, logging of 47,000 hectares of forests, and neglect of 16,000 hectares of vacant land every day. On the other hand, the population growth of 1 billion people per decade is further burdening the planet. This situation demands fundamental changes in various fields, including the preservation of local wisdom. However, the advancement of modern knowledge has caused local wisdom to be increasingly marginalized by most people, so that it can only be found in certain indigenous communities, one of which is the Sampulonrua Indigenous people. This study aims to find out how the Patumbu Katallassang tradition is implemented by the Sampulonrua Indigenous people, analyze the relationship between local wisdom and environmental management in supporting the Sustainable Development Goals 15 Life on Land, and describe the implementation of this traditional event. This study uses qualitative methods with ethnographic and descriptive approaches. Data were obtained through in-depth interviews, participatory observations, and documentation to understand the cultural values underlying the tradition. Data analysis techniques are carried out descriptively with an inductive approach, identifying relevant main themes from field data. The result of this research is that the tradition of Patumbu Katallassang is a tradition found in Bulutana village, Gowa Regency which is the main foundation of the Sampulonrua Indigenous people in managing the natural resources around them. In the tradition of patumbu katalassang, there are two traditional events that are routinely carried out every year, namely appalili and assaukang which are carried out at ballak lompoa. For this reason, Sustainable Developmant Goals 15 Life and Land supports the presence of the Patumbu Katallassang Tradition.